Inverted Solar Cells: Lowering the Work Function of ITO by Covalent Surface Grafting of Aziridine: Application in Inverted Polymer Solar Cells (Adv. Mater. Interfaces 1/2015). Issue 1 (January 2015) - Song, Yingxue; Yan, Li; Zhou, Yi; Song, Bo; Li, Yongfang
<x xml:space="preserve">Abstract</x> Toward high‐performance and stable inverted polymer solar cells, Y. Zhou, B. Song, and co‐workers demonstrate in article 1400397 a facile method to prepare covalently bonded and uniform surface modifications on ITO substrates. Applying surface grafting of aziridine as the interlayer effectively lowers the surface work function of ITO which in turn dramatically improves the device performance and stability. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>